Indonesia’s Economic Growth Forecasting - Muhammad Teguh; Abdul Bashir (Faculty of Economics, Universitas Sriwijaya, 2019)
The high economic growth is very important for Indonesia to accelerate the development process at this period. Although, the growth rate was reached at 5.17 % in 2018 is likely high enough, some domestic economists even point out, it really can be raised to a higher level. This research tries to investigate and formulate again Indonesia’s economic growth rate in 2018 and forecast it for 2019. By doing analysis recent real GDP data by industrial origin and by type of expenditures, and also consider all of the available potential economic resources, this research shows that Indonesia’s economic growth rate could stand at 6.03 % in 2018 and also at 6.03 % in 2019. Anyway, the government need a good economic plan and consistently performing appropriate strategies which are suited to targets in order to have rapid and stable economic growth rate